Ethical Hazards: A Motive, Means, and Opportunity Approach to Curbing Corporate Unethical Behavior - Pendse, Shripad G. (2012)
Scandals in companies such as Enron have been a source of great concern in the last decade. The events that led to a global financial crisis in 2008 have heightened this concern. How does one account for executive behaviors that led to such a crisis? This article argues that a conjunction of motive, means, and opportunity creates ‘an ethical hazard’ making questionable executive decisions more probable. It then suggests that corporate unethical behavior can be minimized by creating a process to identify and remove such ethical hazards, and by appointing an ‘ethical hazards marshal.’
Keywords: Financial Crisis; corporate scandals; Ethical hazards; Incentives; corporate ethics